Child-Friendly Schools Meet Green Education: A Bibliometric Mapping of Trends and Synergies in School Management Research - Jumatul Hidayah; Eka Apriani; Yongki Ramadhan Putra (AL-ISHLAH: Jurnal Pendidikan, 2026)
Research on Child-Friendly Schools (CFS) and Green School initiatives has expanded significantly over the past decade; however, these two frameworks are often examined separately despite their shared emphasis on holistic and sustainable school development. This study aims to map the intellectual structure, research trends, and emerging synergies between child-friendly education and green school management.A bibliometric analysis was conducted on 312 peer-reviewed documents indexed in the Scopus database from 2010 to 2024. Publications were retrieved using structured keyword combinations related to child-friendly schools, green schools, sustainability, and environmental education in school contexts. After data cleaning and keyword normalization, analyses were performed using VOSviewer and Biblioshiny to examine publication trends, citation patterns, co-authorship networks, keyword co-occurrence, and thematic clustering.Findings indicate a marked increase in publications after 2019, reflecting heightened global attention to sustainable and inclusive education aligned with the Sustainable Development Goals. Keyword co-occurrence analysis reveals a thematic shift from infrastructure-oriented sustainability toward holistic approaches integrating student participation, eco-humanism, and whole-school governance models. Four major thematic clusters were identified: green school policies, student participation and behavior, eco-friendly infrastructure, and values-based holistic education. However, collaboration networks remain regionally concentrated, and interdisciplinary integration between child rights and environmental governance research is still limited.The results suggest that integrating child-friendly and green school frameworks offers a promising pathway toward inclusive and sustainability-oriented school management. Future research should prioritize longitudinal, comparative, and interdisciplinary studies to strengthen evidence-based models that align environmental responsibility with child-centered educational principles.